HUBUNGAN PENDIDIKAN DAN PENGETAHUAN PETERNAK KERBAU TENTANG PAKAN DENGAN KETERAMPILAN PETERNAK DALAM PENYEDIAAN PAKAN UNTUK PENGEMBANGAN TERNAK KERBAU DI KABUPATEN PEMALANG - Arif Budiono; Krismiwati Muatip; Pambudi Yuwono (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The purpose of this study was to determine the relationship between farmer education and knowledge of farmers about feed with the skills of farmers in providing buffalo feed in Pemalang Regency. The research target was buffalo breeders in Pemalang Regency. Materials and Method. The sampling method used was purposive random sampling by taking buffalo breeders as respondents in three areas, namely Surajaya Village in Pemalang District, Kejambon Village in Taman District, and Wanarata Village in Bantarbolang District. The data obtained were analyzed using Spearman rank correlation. Results. The results showed that there was a significant relationship between farmer's education and knowledge of farmers about feed with the skills of farmers in providing buffalo feed. The Spearman correlation value between farmer education and farmer skills in providing feed shows a value of 0.372, while between farmer knowledge about feed and farmer skills in providing feed shows a value of 0.582.